The future of Takaful (Islamic Insurance) business in Malaysia under the Islamic Financial Services Act (IFSA) 2013 - Salleh, Safinar; Ibrahim, Uzaimah; Zahraa, Mahdi (AENSI Publications, 2014)
Very recently, a new takaful legislation, i.e. IFSA 2013, has been enforced to repeal the old Takaful Act 1984 (TA). Generally, the 2013 Act strengthens the requirements made under the 1984 Act as well as provides additional requirements including licensing of takaful operator, limiting to one class of takaful business per takaful operator and establishment of permissible takaful interest. The new Act also incorporates requirements that are provided by guidelines related to takaful business especially Shariah-compliant and Shariah governance requirements. This study aims to examine these statutory requirements and analyse their implications on the business of takaful in Malaysia. The traditional legal research method is used to analyse provisions relating to takaful in IFSA. This study finds that the Malaysian takaful law has been substantially improvised by the promulgation of the new Act and many changes need to be done by takaful operators to ensure their compliance with the law. This recent legal development could be a promising initiative for better future of takaful industry in Malaysia.